Monitoring of Measurable Residual Disease in Multiple Myeloma by Multiparametric Flow Cytometry. Issue 1 (17th July 2019) - Soh, Kah Teong; Wallace, Paul K.
Abstract: Recent interest in high‐sensitivity multiple myeloma (MM) measurable residual disease (MRD) testing is a direct consequence of the high‐quality responses achieved using novel therapeutic agents and better treatment strategies. Traditional diagnostic measures such as immunohistochemistry and morphology have detection sensitivities of only 10 −2 to 10 −3, which do not reliably predict progression‐free survival (PFS) or overall survival (OS) after these treatments. Contemporary monitoring of MM MRD has switched to more sensitive platforms such as allele‐specific oligonucleotide quantitative polymerase chain reaction (ASO‐qPCR), next‐generation sequencing (NGS), and multiparametric flow cytometry (MFC). Though both ASO‐qPCR and NGS have excellent detection sensitivities (10 −5 to 10 −6 ), both technologies have lower applicability when compared to MFC. Conventional MFC can easily reach a detection sensitivity of 10 −4 and when optimized can achieve a sensitivity of 10 −5 to 10 −6 . Current consensus guidelines require a minimum of 2 million and recommend 5 million events be acquired to reach a minimum sensitivity of 10 −5 . As conventional immunophenotyping protocols are unable to attain these numbers, alternative MFC staining procedures are required. This article describes two high‐sensitivity MFC approaches that can be used for MM MRD testing. © 2019 by John Wiley & Sons, Inc.